HIGH RATE OF ESBL- PRODUCING ESCHERICHIA COLI FROM RETAIL-CHICKEN CARRYING BLACTX-M GENE ON PLASMIDS MAINLY CARRYING FREPB REPLICON - A. Murtaza 1#; S. Ullah1#; I. Tauseef; K. S. Haleem; M. Jamal; J. Gu; Asadullah; S. Ayaz; M. Shafiq; N. A. Khan; S. U. Rahman4 (Journal of Animal and Plant Sciences, 2020)
Antimicrobial resistance is increasingly reported worldwide, however, there is scarcity of data from Pakistan. Particularly, data from food-producing animals and their products is totally lacking. Here, we report on the ESBL-genotypes, integron types, insertion sequence, plasmid replicon typing and susceptibility to commonly used-antimicrobials of E. coli recovered from poultry-meat in live bird market of District Mardan, Khyber Pakhtunkhwa, Pakistan. Random E. coli isolates were picked up for screening of ESBL-production and -genotype, antimicrobial resistance profile through disc diffusion method and integron and plasmid replicon typing. Of the 33 E. coli multidrug resistant isolates (resistant to tetracycline, ampicillin, cefotaxime and novobiocine), 28 (phylogroup B2=11, A=9 and D=8) were ESBL producers harboring blaCTX-M (blaCTXM-9=25 and blaCTXM-1=3, blaCTXM-15=3), while, none of them were carrying blaSHV or blaTEM. Majority of these ESBL producers were carrying class-1 integron (n=21), although 11 isolates were carrying ISCR1, which found to be linked with blaCTX-M among 5 isolates (45.5%). PCR based plasmid replicon typing revealed that FrepB replicon was found most dominantly and carried by 27 isolates followed by B/O replicon. This suggests that poultry raw meat may contribute to spread of ESBL-producing E. coli or ESBL- genes.
Keywords: ESBL; food-producing animals; integron; replicon typing; ISCR; multidrug resistant; E